Effects of Different Phosphorus Application Rates in Wheat Season on Crop Yield and Phosphorus Efficiency in Wheat-Maize and Wheat-Soybean Rotation Systems - KOU Xinyue; SANG Lizhi; SHEN Yufang (Shuitu Baochi Xuebao)
[Objective] In order to study the effects of different phosphorus application rates in wheat season on crop yield and phosphorus fertilizer efficiency in different crop rotation systems in Guanzhong area of Shaanxi Province, the appropriate phosphorus fertilizers application rates in wheat season were defined to achieve high yield and high efficiency of crops in different rotation systems. [Methods] Two crop rotation systems, wheat-maize and wheat-soybean, were selected as the research objects, and five phosphorus application rates (P2O5) (0, 75, 150, 225, and 300 kg/hm2) were set. The annual crop yield, phosphorus fertilizer utilization efficiency, soil available P content and their relationships with phosphorus application rates were analyzed in 2021-2022 and 2022-2023. [Results] Compared with no phosphorus application (0 kg/hm2), only phosphorus application in wheat season significantly increased the annual yield of wheat, maize, soybean and annual yield of wheat-maize and wheat-soybean crop rotation systems (p<0.05), and the annual yield and phosphorus fertilizer efficiency of crop rotation reached a high level. The annual yield of the two crop rotation systems was the highest in the 150 kg/hm2 treatment, and the wheat-maize crop rotation system was significantly higher than the 75 kg/hm2 treatment (p<0.05), but there was no significant difference between wheat-soybean crop rotation and 75 kg/hm2 treatment. The soil available P content of the wheat yield of wheat-maize and wheat-soybean crop rotation systems was 20.07, 16.15 mg/kg, respectively. The agronomy efficiency, partial productivity, recovery rate and phosphorus efficiency index (PEI) of phosphorus fertilizer in the two crop rotation systems decreased with the increase of phosphorus application rate. The PEI of wheat-maize and wheat-soybean rotation systems with 75 kg/hm2 P application were 1.24, 2.02 times of 150 kg/hm2 P application, respectively, and the PEI of wheat-soybean rotation system decreased more significantly. Considering food security, environmental security and fertilizer utilization rate, and taking 95% of the maximum wheat yield as the actual target, the corresponding P application rates of wheat-maize and wheat-soybean rotation systems were 115, 95 kg/hm2, respectively, which could achieve phosphorus recovery efficiency and low phosphorus surplus, and ensure that the annual yield of wheat-maize and wheat-soybean rotation systems reached 96.23% and 95.43% of the maximum yield, respectively; the wheat-soybean rotation system had a lower P application requirement. [Conclusion] For different rotation systems, reasonable P application should be carried out from the perspective of crop yield, fertilizer efficient utilization and zero surplus management policy, so as to meet the coordinated supply of crop-soil P nutrients to ensure high yield while improving P efficiency.